Diameter of ovarian follicles, estradiol, and progesterone concentrations, and pregnancy rates in cattle treated with progestins and PGF - M.W Smith; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1994)
Holstein cows and virgin heifers were treated with progestins and PGF before first 2a service to determine their influence on reproductive traits. Control cows were given two injections of PGF 14 days apart and 2a inseminated at estrus after the second injection. Two groups received a norgestomet ear implant (N1) or a progesterone-releasing intravaginal device (PRID; P1) 8 days after one injection of PGF , followed the next day by PGF to 2a 2a regress the corpus luteum, and the progestin source was removed 7 days later. The last two treatments were similar except the second injection of PGF was given 14 days after the 2a first and norgestomet (N6) or PRID (P6) sources were removed 1 day later. Inseminations were performed at estrus in the latter four treatments. Pregnancy rates and serum progesterone were higher and serum estradiol and follicular diameters were lower in controls, P6, and N6 treatments, where the corpus luteum was functional during progestin treatments, than in those treatments where the corpus luteum was absent (P1 and N1). Follicle turnover occurred more consistently in control, P6, and N6 treatments, whereas when follicular diameter and serum estradiol were greater (N1 treatment), turnover did not occur as often and pregnancy rates at first service were reduced markedly. Treatments with progestins must control follicular growth, or fertility will be reduced.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; PGF; Progestins; Follicels; Fertility